The Problems of Conception of Law Amendment with Government Regulations of Omnibus Bill on Job Creation Studied from the Theory of Legislation Perspective - Zainuddin Zainuddin (Randwick International of Social Science Journal, 2020)
Crucial issues in the Omnibus Bill on Job Creation are the actual discussion today. In particular, the potential for executive heavy in Article 170 paragraph (1) of Omnibus Bill on Job Creation is because the Law could be amended by a Government Regulation. This paper trues to analyze the problems of conception in the Omnibus Bill on Job Creation and also the problems in the perspective of statutory theory. The research method used is normative juridical legal research. The results show that Article 170 paragraph (1) of Omnibus Bill on Job Creation contradicts Article 7 of Law no. 12 of 2011 and the theory of legislation put forward by Adolf Merkl and Hans Kelsen's theory of norms level.